The role of Gut Microbiota in the development of obesity and Diabetes. Issue 1 (December 2016) - Baothman, Othman; Zamzami, Mazin; Taher, Ibrahim; Abubaker, Jehad; Abu-Farha, Mohamed
Abstract Obesity and its associated complications like type 2 diabetes (T2D) are reaching epidemic stages. Increased food intake and lack of exercise are two main contributing factors. Recent work has been highlighting an increasingly more important role of gut microbiota in metabolic disorders. It's well known that gut microbiota plays a major role in the development of food absorption and low grade inflammation, two key processes in obesity and diabetes. This review summarizes key discoveries during the past decade that established the role of gut microbiota in the development of obesity and diabetes. It will look at the role of key metabolites mainly the short chain fatty acids (SCFA) that are produced by gut microbiota and how they impact key metabolic pathways such as insulin signalling, incretin production as well as inflammation. It will further look at the possible ways to harness the beneficial aspects of the gut microbiota to combat these metabolic disorders and reduce their impact.